Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.redox.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate-induced mitophagy alters cellular redox status

Abstract: Artesunate (ART) is a prominent anti-malarial with significant anti-cancer properties. Our previous studies showed that ART enhances lysosomal function and ferritin degradation, which was necessary for its anti-cancer properties. ART targeting to mitochondria also significantly improved its efficacy, but the effect of ART on mitophagy, an important cellular pathway that facilitates the removal of damaged mitochondria, remains unknown. Here, we first observed that ART mainly localizes in the mitochondria and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 38 publications
(65 reference statements)
6
58
0
1
Order By: Relevance
“…Using an ART probe with an alkyne moiety, we confirmed the direct interaction of ART with PINK1 and parkin. Our results also showed that ART stabilizes PINK1, and the resultant accumulation of mitochondrial PINK1 enhances the phosphorylation of ubiquitin to activate Parkin . These damaged mitochondria are selectively removed by mitophagy …”
Section: Mitophagy Induction By Artesunatesupporting
confidence: 66%
See 4 more Smart Citations
“…Using an ART probe with an alkyne moiety, we confirmed the direct interaction of ART with PINK1 and parkin. Our results also showed that ART stabilizes PINK1, and the resultant accumulation of mitochondrial PINK1 enhances the phosphorylation of ubiquitin to activate Parkin . These damaged mitochondria are selectively removed by mitophagy …”
Section: Mitophagy Induction By Artesunatesupporting
confidence: 66%
“…In the process of mitophagy, these ubiquitinated mitochondrial proteins are recognized by autophagy receptors such as SQSTM1/p62 or other molecules that interact with LC3 to form autophagosomes . We identified the involvement of the PINK1‐parkin pathway in ART‐induced mitophagy (Figure ) . Using an ART probe with an alkyne moiety, we confirmed the direct interaction of ART with PINK1 and parkin.…”
Section: Mitophagy Induction By Artesunatesupporting
confidence: 52%
See 3 more Smart Citations